2018
DOI: 10.1016/j.nicl.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subcortical resting-state functional connectivity in patients with psychophysiological insomnia after cognitive–behavioral therapy

Abstract: Study objectivesTo examine the resting-state functional connectivity (FC) between subcortical regions in relation to whole-brain activity in patients with psychophysiological insomnia (PI) and changes following cognitive–behavioral therapy for insomnia (CBTi).MethodsThe FC between subcortical seed regions (caudate, putamen, pallidum, amygdala, thalamus, and hippocampus) and whole-brain voxels were compared between the PI group (n = 13, mean age: 51.0 ± 10.2 years) and good sleepers (GS, n = 18, mean age: 42.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 40 publications
6
39
1
1
Order By: Relevance
“…Convergent findings based on functional MR imaging support that spontaneous neural activity or FC in the insular cortex, prefrontal cortex and precuneus were disrupted in patients with insomnia or subjects with insomnia symptoms [6][7][8][9][10][11][12]. In line with previous findings, our study firstly showed that these regions also have high classification weights.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Convergent findings based on functional MR imaging support that spontaneous neural activity or FC in the insular cortex, prefrontal cortex and precuneus were disrupted in patients with insomnia or subjects with insomnia symptoms [6][7][8][9][10][11][12]. In line with previous findings, our study firstly showed that these regions also have high classification weights.…”
Section: Discussionsupporting
confidence: 91%
“…Neuroimaging studies for insomnia have made substantial effort to understand the neuromechanisms of insomnia. Previous studies found aberrant brain metabolism and connectivity related to the prefrontal cortex, insular cortex, amygdala, precuneus and caudate in primary insomnia [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, using PET, Nofzinger et al [4] found smaller decrease in relative metabolism from waking to non-REM sleep states in the ascending reticular activating system, hypothalamus, thalamus, insular cortex, amygdala, hippocampus, anterior cingulate and medial prefrontal cortices, which supports the CNS hyperarousal hypothesis.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although CBT-I does not have the specific aim to improve other psychiatric symptoms such as depression or anxiety, many studies on insomnia comorbidities and mental illness suggest that it still has a good effect on mood [32,33]. e CBT mechanism may reduce the functional connection between the thalamus and parietal cortex, the putamen and motor cortex, and the amygdala and lingual gyrus and enhance the functional connection between the caudate nucleus and supramarginal gyrus, the globus pallidus and orbital frontal cortex, and the hippocampus and frontal parietal gyrus [34]. e specific acupoints used can also adjust the mood, which has been confirmed by many Evidence-Based Complementary and Alternative Medicine 9 modern studies, and the single-point studies of DU-20, HT-7, and BL-62, which were selected in this study, have been confirmed to have the effect of adjusting emotions and are widely used in the clinical treatment of mental and emotional illness [35,36].…”
Section: Ea Combined With Cbt Erapymentioning
confidence: 99%
“…Previous study found that the prefrontal lobe was hypo-activated during a verbal fluency task and was recovered after the CBT (18). The brain region of the visual area and the amygdala showed an increased functional connectivity before the CBT, whereas the functional connectivity between the two areas was decreased after the CBT (19). These findings suggest that the individuals with chronic insomnia symptoms have an overreaction to visual stimuli before the CBT while it was recovered after the CBT.…”
mentioning
confidence: 76%